Impacto de la misión de entrenamiento de la Unión Europea sobre la crisis maliense - GALLARÍN LÓPEZ, Ana (Journal of the Spanish Institute for Strategic Studies, 2023)
The European Union, as regional actor that seeks to increase its presence and influence in international crisis management, opted for reforming the Malian defense sector through the instruction, training and advice of its troops. However, deep political crisis, internal conflicts, and the growing loss of confidence of citizens in its institutions, together with the rise of jihadism, have been a tough obstacle for European troops since the beginning of the European mission which, since the beginning of operations, have witnessed the general worsening of the situation in the country. Consequently, it is worth questioning the real effectiveness of the strategy chosen by Europe on Malian soil in terms of defense, with the aim of developing better adapted responses to the true reality of the conflict, through the analysis of the results obtained by EUTM-Mali after nine years of intervention.